Contextual teaching and learning approach to supplementary reading materials based on 2013 Curriculum - Titik Saryati; Yuyun Yulia (Journal of English Language and Pedagogy, 2019)
The objectives of this study are to (1) develop supplementary reading materials using Contextual Teaching and Learning Approach for students of SMP N 1 Moyudan and (2) describe the Â efficacy of the supplementary reading materials. This research belongs to Educational Research and Development (R&D) using a simplified six steps of (Gall, Gall, & Borg, 2003) model. The finding shows that the students learn English to achieve the 2013 curriculum learning objectives. The necessities of the teaching and learning English is to improve students' English skills so that they gain good score for the national examinations though students have less motivation to learn reading and they cannot learn independently. They cannot differentiate or understand WH-questions that is important in learning reading. The efficacy of this product helps students to improve their reading skill especially to understand the topic, the generic structure, the main idea, the grammar and the vocabulary used in the text. The supplementary reading materials as the product of this study provide additional learning resources for students.